SERIAL ACQUIRERS AND LONG-TERM STOCK PRICE REACTIONS - Malikova, Anel (Nazarbayev University Graduate School of Business, 2023)
This thesis explores the long-term impact of serial acquisitions on acquirers' stock performance, focusing on UK and European companies from January 2000 to August 2024. Using event study methodologies, including event dummy regressions and a modified Almon-lag approach, the study uncovers patterns in stock price behavior following acquisitions. The findings reveal that while UK acquirers experience immediate positive market reactions, European acquirers, particularly in Milan and Euronext, show prolonged but delayed positive effects. Market factors consistently influence excess returns, emphasizing the role of broader market dynamics. However, industry-level analysis highlights significant heterogeneity, with some results constrained by sample sizes. This research provides valuable insights into the stock price dynamics of serial acquirers, offering implications for corporate growth strategies and financial markets.
Серийные приобретатели и долгосрочные реакции на цены акций
Сериялық сатып алушылар және олардың акция бағаларына ұзақ мерзімді әсері
Keywords: M&A; Serial acquirers; CARs; Type of access: Embargo